PERLINDUNGAN HUKUM TERHADAP KREDITUR ATAS PERJANJIAN KAWIN YANG DIBUAT SETELAH PERKAWINAN - Cokorde Istri Dian Laksmi Dewi (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2021)
This is derived from the Constitutional Court Decision Number 69/PUU-XII/2015, to change is a practice making of a marriage agreement, where before the marriage agreement be made before or when the marriage, as is the Constitutional Court Decision Number 69/PUU-XII/2015 the marriage agreement can be made the marriage agreement at the time of marriage. The changer these norms give a legal impact against to legal events wicht has accurred previously related to third parties of creditors. The problem of legal protection for creditors due to the making of marriage agreement during marriage can be answered for the conducting legal research using the normative juridical legal research method, which refers to formal legal sources. so that the research method can protect creditors from the marriage agreement made during the marriage is with preventive and repressive legal protection, preventive is taking precautions that can be done with the precautionary principle of a creditor before giving credit to the debtor and resolving the problem through legal channels by canceling the marriage agreement or making a civil suit to the district court, as long as the creditor can prove that the marriage agreement was made after an incident occurred. the law with the creditor or the marriage agreement causes a loss to the creditor.